1998
DOI: 10.1044/jslhr.4103.688
|View full text |Cite
|
Sign up to set email alerts
|

The Socioemotional Behaviors of Children With SLI

Abstract: Two models of the relationship between socioemotional behavior and verbal abilities are compared: Social Adaptation and Social Deviance. The socioemotional integrity of 17 children with specific language impairment (SLI) and 20 unaffected children who were age-matched (AM) was examined using the Child Behavior Checklist (CBCL) and the Teacher's Report Form (TRF) at kindergarten and first grade. All CBCL and TRF syndrome scale means for both groups were within normal limits. Significant group x respondent inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
183
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(209 citation statements)
references
References 34 publications
21
183
1
4
Order By: Relevance
“…Some have suggested that language difficulties cause an impairment in social cognition (e.g., de Villiers & de Villiers, 2000) and there is some compelling intervention work to support this (Hale & Tager Flusberg, 2003). On the other hand, the wealth of research showing that those with SLI have social difficulties (e.g., Cantwell & Baker, 1978;Redmond & Rice, 1998;Conti-Ramsden & Botting, 2004;Fujiki et al, 2001), also opens the question as to whether these could arise from either inherent (co-morbid) social cognitive impairments or psychosocially as a result of poor language opportunities.…”
Section: Social Cognition In Relation To Social Skill and Language Inmentioning
confidence: 99%
“…Some have suggested that language difficulties cause an impairment in social cognition (e.g., de Villiers & de Villiers, 2000) and there is some compelling intervention work to support this (Hale & Tager Flusberg, 2003). On the other hand, the wealth of research showing that those with SLI have social difficulties (e.g., Cantwell & Baker, 1978;Redmond & Rice, 1998;Conti-Ramsden & Botting, 2004;Fujiki et al, 2001), also opens the question as to whether these could arise from either inherent (co-morbid) social cognitive impairments or psychosocially as a result of poor language opportunities.…”
Section: Social Cognition In Relation To Social Skill and Language Inmentioning
confidence: 99%
“…In addition, studies have indicated that these children are more likely to show higher levels of withdrawn behavior as reported by teachers (Fujiki, Brinton, Morgan, and Hart, 1999;Redmond and Rice, 1998) and observed during free play settings (Fujiki, Brinton, Isaacson, and Summers, 2001). The factors responsible for children's reluctance to participate are both social and grammatical.…”
Section: Introductionmentioning
confidence: 89%
“…Developmental language disorders (DLD), including specific language impairment, can give rise to severe problems in later ToM development as advanced levels of ToM depend on intact language development. Children with DLD display deficits in falsebelief understanding, which persist in adult life (79). Although general grammatical development and vocabulary contribute significantly to ToM reasoning (80), impairment of grammar does not preclude a sound development of ToM, particularly in children with normal comprehension.…”
Section: Real-life Consequences Of Tom Development and Clinical Condimentioning
confidence: 99%